Effect of Artemisia vulgaris Extract on VEGF Expression, CD34, Microvascular Density, and Diameter of Mammary Adenocarcinoma Tumors: In vivo Study - Putri Endah Puspitaningtyas; Subiyakto (HM Publisher, 2022)
Background. Breast cancer in Indonesia still has a high incidence. Surgery remains the main choice with other modalities such as chemotherapy, radiation, and immunotherapy such as Artemisia vulgaris (AV). This study aimed to prove that administration of AV extract reduced VEGF expression, CD34 and microvascular density (MVD), and tumor diameter in mammary adenocarcinoma. Methods. This study used a